IMPLIKASI FILSAFAT POSITIVISME TERHADAP ILMU HUKUM DAN PENEGAKANNYA - Wiguna, Made Oka Cahyadi (Program Magister Ilmu Hukum Universitas Ekasakti, 2023)
Positivism has developed and dominated the flow of legal thought to this day. This study aims to examine the implications of positivism for law and its enforcement. The implications of positivism for the development of jurisprudence put the system of legislation into its ontological aspects. The epistemology is doctrinal-deductive putting his argument on the application of the structure of positive norms into the structure of concrete legal cases. The consequence is on the axiological aspect, it only craves legal certainty. Law enforcement in Indonesia which is influenced by legal positivism seems to fail to bring about justice. On many occasions it shows that it has not been able to combine legal certainty and justice. Judges in deciding a case, tend to only consider the sound of the law, without considering the values or norms that live in society.